(untitled) (Research, Society and Development, 2022)
Systemic Arterial Hypertension (SAH) is a multifactorial chronic disease, where the patient will present cases of persistent elevation of blood pressure levels, equal to or above 140/90 mmHg. This disease is one of the main cardiovascular risk factors and is highly prevalent in almost all countries. Such pathology can be exacerbated in the dental office since the scenario can trigger stressful situations such as anxiety. In addition, during or after dental procedures, drugs that may interfere with the vascular system, such as vasoconstrictors or drugs that interact with the function of antihypertensive drugs, may be administered. This is an epidemiological, descriptive, cross-sectional study with a quantitative approach, where the target population consisted of hypertensive patients from a Dental Clinic of a University in the South of Minas Gerais, in order to evaluate the therapeutic protocols used during care. dental. The collected data were organized and presented through tables, computing the absolute and percentage frequencies. Information on blood pressure values, procedures performed, gender, age group, antihypertensive drugs and complications after treatment were collected from the medical records. An incidence of 20.8% of hypertensive patients was observed in relation to dental treatment, where 63.19% of the analyzed sample of hypertensive patients are female and 36.81% are male patients. Arterial hypertension represents a high risk for society. Therefore, attention and responsibility of dental professionals and academics with this group of patients is necessary.